ANALISIS KEMAMPUAN PENALARAN MATEMATIS DITINJAU DARI GAYA BELAJAR SISWA SMP PADA MATERI BANGUN RUANG SISI DATAR - Dwi Anggani, Nadiva; Sudihartinih, Eyus (Universitas Insan Budi Utomo, 2024)
The purpose of this study is to describe the results of the analysis of the ability of mathematical reasoning in understanding the building material of flat side spaces reviewed from the learning style of high school students. The study participants consisted of four students who were randomly selected at some high school in Java Island. The instruments used are mathematical reasoning skills tests, learning style lifts, and interviews. Based on the results of the study, it was found that students' ability to reason mathematically varied according to the interests of each student's learning style. Students with an auditorium learning style tend to have high reasoning skills, they are superior in indicators presenting mathematical statements, giving reasons or evidence against the truthfulness of answers or declarations, drawing conclusions/making generalizations. Therefore, for future researchers to study further with a larger number of participants, and the research is done offline so the results are more valid.